(untitled) (Research, Society and Development, 2021)
Objective: this study compared the force degradation and color change of esthetic elastomeric chains of four commercial brands. Materials and methods: the study analyzed 10 medium-force esthetic elastomeric chains with 6 links of Morelli, Orthometric, Eurodonto and 3M brands from sealed packages within the expiration date. The elastics were stretched twice their length, according to the manufacturer’s recommendations, and were immersed in artificial saliva at 37°C. The forces were measured with an orthodontic dynamometer at onset and at intervals of 1, 7, 14, 21 and 30 days after immersion. The force degradation was evaluated calculating the percentage of force lost in relation to the initial force in each time interval, for each group tested separately and also between them. The color change was evaluated by visual analysis scale by observation of photographs of chain elastics before and after study completion by 31 examiners. The ANOVA test of repeated measures was applied considering 2 factors, time and groups, and the Tukey test was used for analysis of multiple comparisons. A significance value of 0.05% was adopted for the analyses. Results: the elastics showed great force degradation. After 7 days the groups presented degradation around 50% of the initial force. In the evaluation between groups, the elastics showed significantly different mean forces. When assessing color change, the scores assigned by examiners evidenced less color changes for elastics of Eurodonto brand. Conclusion: regardless of the commercial brand, transparent elastomeric chains show significant force degradation values ​​after 1 day. The scores assigned to color change evidenced that all commercial brands showed staining, with the best results for Eurodonto elastics.